Effect of carbohydrate and caffeine ingestion on badminton performance following fatiguing exercise - Clarke, N. D.; Duncan, M. J. (World Badminton Federation, 2016)
To successfully compete in sports such as badminton, players must accelerate, decelerate, change direction, move quickly, maintain balance, and repeatedly generate optimum stroke production. However, the mechanism by which fatigue influences badminton performance largely relates to a decrease in shot accuracy combined with weak positional play. The addition of carbohydrate to the fluid ingested prior to and during exercise can improve exercise performance, possibly due to the sparing of muscle glycogen and maintaining blood glucose and carbohydrate oxidation during intermittent exercise. In addition, previous studies suggest that compared with fluid alone, carbohydrate ingestion is able to maintain badminton serve accuracy following fatiguing exercise (Bottoms et al., 2012). Similarly, caffeine supplementation has been reported to increase tennis serve velocity, specifically during the final stages of the simulated match (Hornery et al., 2007). Furthermore, the combined effect of a caffeine and carbohydrate solution has been show to improve sprinting performance, jumping, and the subjective experiences of players during intermittent exercise (Gant et al., 2010). Therefore, the aim of the present study was to investigate the effect of ingesting carbohydrate and caffeine on measures that are central to success in badminton